PEMANFAATAN SOFTWARE MAPLE UNTUK MENINGKATKAN KEMAMPUAN KALKULUS MAHASISWA - Davi Apriandi; Ervina Maret Sulistyaningrum (IKIP PGRI MADIUN, 2015)
Calculus is a compulsory subject for all students of Mathematics Department of IKIP PGRI Madiun. Calculus is very important and must be mastered by the students, because it is very essential as a prerequisite subject in mathematics. In fact, mathematics students still have low ability of calculus. This low ability seen from the results of students' tests. The result of the students' test still low.The result of the test inseparable from the role of lecturer . Lecturer rarely use of instructional media in teaching learning process, whereas learning media can help the understanding of the concept of the student. One of the learning media that can help students to understand the concepts of calculus is Maple software. The aim of this study is improving the ability of students to apply Maple software in learning calculus. This research is Classroom Action Research (CAR). Data collection techniques used were observation, interview, test and documentation. The data analysis techniques are quantitative and qualitative descriptive analysis. The results of the research are the increasing ofaverage value from pretest to the first cycle. The same condition also happens from the first cycle to the second cycle. The average value of pretest is 57,44 among 36 students in less criteria. The average value of the first cycle is 64,94 in a sufficient criterion. The average value of the second cycle is 71,03 ingood criteria. In addition, in interview students give positive response to the process of learning by using Maple software.